Thermal efficiency assessment of MPCM and sand in two concentric cylinders pulsating fluidized bed - Amin Salehianfard; Mohammad Reza Assari; Milad Setareh; Hassan Basirat Tabrizi (Discover Applied Sciences)
Abstract Fluidized beds are widely used in various industrial processes due to their excellent characteristics in drying, chemical reactors, solids separation, fluid catalytic cracking and combustion. Integrating phase change materials (PCMs) into fluidized beds offers a promising solution for thermal energy storage, effectively absorbing and storing thermal energy from periodic or alternating heat sources as latent heat. This technology holds significant potential for enhancing thermal energy storage capabilities of the fluidized beds., The thermal energy storage and charging and discharging efficiencies of MPCM in a pulsating fluidized bed comprising two concentric pipes have not been investigated yet. This study investigates a solid–gas pulsed fluidized bed consisting of two concentric pipes filled with microencapsulated phase change material (MPCM) and sand as the thermal energy storage system. Experiments are carried out to measure the thermal energy storage between the inner pipe containing sand and the MPCM-containing bed, analyzing the effects of the input velocity and pulsation frequency on the energy storage and recovery efficiencies of the MPCM-containing bed. Experiments are performed at three inlet velocity to minimum fluidization velocity (U/U mf) ratios of 1.1, 1.3, and 1.5, and three frequencies of 1.0, 2.5, and 5.0 Hz. Results indicate that the pulsating fluidized bed has higher thermal energy storage and recovery efficiencies than the continuous fluidized bed. Moreover, the thermal energy storage efficiency increases as the U/U mf and pulsation frequency increase; is maximized to 86.01% at a U/U mf of 1.5 and frequency of 5 Hz. In addition, higher frequencies accelerate the charging process, and the bed reaches the stabilized temperature in a shorter time. It is found that the efficiency of thermal energy recovery increases as the frequency increases and the U/U mf reduces. The maximum efficiency of thermal energy recovery is equal to 94.02% at a U/U mf of 1.1 and a frequency of 5 Hz.